The 4M (Look-Organize-Spell-Read) Intervention to Improve Reading Accuracy in Slow Learners: A Single-Case Study - Massitoh, Isnaini Rakhmi Khoirunnisa; Haryanta, Haryanta (Faculty of Psychology, Universitas Gadjah Mada, 2026)
This single-case study aimed to evaluate the effectiveness of the 4M intervention in improving reading accuracy among slow learners with reading challenges. The participant in this study was an 11-year-old student, identified as a slow learner with documented difficulties in accurate reading. The single-case experimental design was employed, with data collected through observation. The 4M intervention, grounded in a behavioral approach, was administered through four key phases: 1) alphabet familiarization; 2) pre-assessment; 3) intervention; and 4) post-assessment. Visual analysis and pre- and posttests were used to assess the program’s effectiveness, with A-B graphs. The intervention reduced the participant’s task completion time—from 15 minutes, 35 seconds to 10 minutes, 23 seconds—for reading 69 concrete words on flashcards. Reading accuracy for 69 concrete words also improved, from 16 words to all 69 correctly read post-intervention.